1990
DOI: 10.1007/bf00011694
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of biocontrol of soil-borne plant pathogens by Rhizobacteria

Abstract: Bacterial antagonism, responsible for biological control, may operate by antiobiosis, competition or parasitism. Parasitism relies on lytic enzymes for the degradation of cell walls of pathogenic fungi. Serratia marcescens was found to be an efficient biocontrol agent of Sclerotium rolfsii and Rhizoctonia solani under greenhouse conditions. Populations of 105 or 106 colony forming units g-1 soil were the most effective. Drench and drip application of S. marcescens suspension were more effective in controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0
6

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(53 citation statements)
references
References 50 publications
(11 reference statements)
2
43
0
6
Order By: Relevance
“…4), a result that is in line with previous studies (15,42). It has been indicated that the biocontrol of fungi can be attributed mainly to the production of antifungal compounds, nutrient competition between antagonists and pathogens, and secretion of extracellular enzymes that degrade fungal cell walls (57). The results of the present study also suggest that red soil actinomycetes may impose antagonistic effects on pathogenic fungi through the production of polyether ionophores, siderophores, and chitinases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…4), a result that is in line with previous studies (15,42). It has been indicated that the biocontrol of fungi can be attributed mainly to the production of antifungal compounds, nutrient competition between antagonists and pathogens, and secretion of extracellular enzymes that degrade fungal cell walls (57). The results of the present study also suggest that red soil actinomycetes may impose antagonistic effects on pathogenic fungi through the production of polyether ionophores, siderophores, and chitinases.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the purified polyethers (e.g., nigericin and nanchangmycin) without exception exhibit strong antifungal activity, while other, coproduced metabolites (e.g., elaiophylins and milbemycins) showed very weak, if any, activity against fungi in our tests. These facts indicate that polyether ionophores account for most of the antifungal activity of these isolates, for polyethers are able to transport cations across plasma membranes and lead to depolarization and succedent cell death (25,57). Although polyene macrolide antibiotics are well known as antifungal agents (60), in our study, only two isolates were found to produce this type of compound.…”
Section: Discussionmentioning
confidence: 54%
“…Hence other secondary metabolites produced by the strain IC14, which were not chitinases, played a key role in the biocontrol activity, atleast against Botrytis cinerea and S. sclerotiorum. However, biocontrol action of S. marcescens against S. rolfsii and R. solani was attributed to solely due to chitinase activity 32 . Comparison of Chi A negative mutant strain C5 with the wild type strain 34S1 in Stenotrophomonas maltophila for biocontrol of root rot infecting fungus Magnaporthe poae resulted in no obvious differences in its growth inhibition in vitro conditions.…”
Section: Discussionmentioning
confidence: 99%
“…According to Cook and Baker (1983), "Biological control is the reduction of the amount of inoculum or diseaseproducing activity of a pathogen accomplished by or through one or more organisms other than man." There are multiple mechanisms by which naturally occurring beneficial bacteria and fungi can suppress disease incidence or severity, including antibiosis, competition for nutrients and space, and the production of lyctic enzymes (Weller 1988;Chet et al 1990;Chet and Inbar 1994;Handelsman and Stabb 1996;Raaijmakers et al 2002;Haas and Defago 2005;Van Loon 2007). Of special interest is the enhancement of plant innate defense responses against pathogens by beneficial bacteria and fungi that occur naturally on plant roots (Zehnder et al 2001;Kloepper et al 2004;Hoitink et al 2006;Van Wees et al 2008;Segarra et al 2009).…”
mentioning
confidence: 99%